Neurorestorative Therapy for Stroke - Chen, Jieli; Venkat, Poornima; Zacharek, Alex; Chopp, Michael (Frontiers in Human Neuroscience, 2014)
Ischemic stroke is a major cause of death and long-term disability world wide. Development of effective therapy has been the target of intense research. Accumulating preclinical literature has shown that substantial functional improvement after stroke can be achieved using subacutely administered cell-based and pharmacological therapies. This review provides an update on bone marrow-derived mesenchymal stem cells (BMSCs), human umbilical cord blood cells (HUCBCs) and select pharmacological agents presently in clinical use for other indications, to promote recovery processes in the sub-acute and chronic phases after stroke. This review paper also focuses on molecular mechanisms underlying the cell-based and pharmacological restorative processes which enhance angiogenesis, arteriogenesis, neurogenesis and white matter remodeling following cerebral ischemia as well as an analysis of the interaction/coupling among these restorative events. In addition, the role of microRNAs (miRNAs) mediating the intercellular communication between exogenously administered cells and parenchymal cells, and their effects on the regulation of angiogenesis and neuronal progenitor cell proliferation and differentiation, and brain plasticity after stroke will be described.